2016
DOI: 10.35790/eg.4.2.2016.13924
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan tingkat pengetahuan tentang kesehatan gigi dan mulut dengan status karies gigi pada penyandang tunanetra

Abstract: Blind people have limited ability to receive any knowledge through their sight. A false perception can lead to wrong actions including the act of oral health maintenance, therefore, the risk of oral diseases such as caries, is higher in blind people than in normal ones. This study was aimed to determine the relationship between the level of oral health knowledge and caries status. Respondents were selected by using total sampling technique. This was a descriptive analytical study with a cross sectional design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
5
0
11
Order By: Relevance
“…Appropriate knowledge of dental and oral cleansing procedures represents the basis for maintaining oral hygiene. 18 The attitude towards and practice of maintaining dental health were shown not to have a significant relationship with the CI. A study in 2009 also reported to have found no significant correlation between attitude and the dental CI.…”
Section: Discussionmentioning
confidence: 86%
“…Appropriate knowledge of dental and oral cleansing procedures represents the basis for maintaining oral hygiene. 18 The attitude towards and practice of maintaining dental health were shown not to have a significant relationship with the CI. A study in 2009 also reported to have found no significant correlation between attitude and the dental CI.…”
Section: Discussionmentioning
confidence: 86%
“…Kesehatan gigi dan mulut yang terganggu bisa menjadi tanda atau bahkan bisa menjadi faktor timbulnya gangguan bagi kesehatan. [1] Kesehatan gigi dan mulut merupakan bagian dari kesehatan secara keseluruhan yang perlu diperhatikan oleh masyarakat. Masalah kesehatan gigi dan mulut yang sering terjadi yaitu karies.…”
Section: Pendahuluanunclassified
“…Lack of knowledge will lead to bad behavior and attitudes towards the maintenance of dental and oral health. 10,11 On the other hand, good and correct knowledge in maintaining and maintaining dental and oral health will realize oral hygiene good which shows the overall health status of the individual. 12 Good knowledge of the COVID-19 pandemic and oral hygiene as an effort to prevent the transmission of COVID-19 is important to apply during this pandemic.…”
Section: Covid-19 Pandemic (Coronavirus Disease 2019)mentioning
confidence: 99%